Effectiveness of two coronavirus disease 2019 (COVID-19) vaccines (viral vector and inactivated viral vaccine) against severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection in a cohort of healthcare workers. (30th March 2022) - Marra, Alexandre R.; Miraglia, João Luiz; Malheiros, Daniel Tavares; Guozhang, Yang; Teich, Vanessa Damazio; da Silva Victor, Elivane; Pinho, João Renato Rebello; Cypriano, Adriana; Vieira, Laura Wanderly; Polonio, Miria; Ornelas, Rafael Herrera; de Oliveira, Solange Miranda; et al.
Abstract: Objective: We investigated real-world vaccine effectiveness for Oxford-AstraZeneca (ChAdOx1) and CoronaVac against laboratory-confirmed severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection among healthcare workers (HCWs). Methods: We conducted a retrospective cohort study among HCWs (aged ≥18 years) working in a private healthcare system in Brazil between January 1, 2021 and August 3, 2021, to assess vaccine effectiveness. We calculated vaccine effectiveness as 1 − rate ratio (RR), with RR determined by adjusting Poisson models with the occurrence of SARS-CoV-2 infection as the outcome and the vaccination status as the main variable. We used the logarithmic link function and simple models adjusting for sex, age, and job types. Results: In total, 13, 813 HCWs met the inclusion criteria for this analysis. Among them, 6, 385 (46.2%) received the CoronaVac vaccine, 5, 916 (42.8%) received the ChAdOx1 vaccine, and 1, 512 (11.0%) were not vaccinated. Overall, COVID-19 occurred in 6% of unvaccinated HCWs, 3% of HCWs who received 2 doses of CoronaVac vaccine, and 0.7% of HCWs who received 2 doses of ChAdOx1 vaccine ( P < .001). In the adjusted analyses, the estimated vaccine effectiveness rates were 51.3% for CoronaVac, and 88.1% for ChAdOx1 vaccine. Both vaccines reduced the number of hospitalizations, the length of hospital stay, and the need for mechanical ventilation. In addition, 19 SARS-CoV-2 samples from 19 HCWs were screened for mutations of interest. Of 19 samples, 18 were the γ (gamma) variant. Conclusions: Although both COVID-19 vaccines (viral vector and inactivated virus) can significantly prevent COVID-19 among HCWs, CoronaVac was much less effective. The COVID-19 vaccines were also effective against the dominant γ variant.